Pengaruh Brand Loyalty, Brand Love, Brand Commitment Terhadap Willingness To Pay A Premium Price - Trisno Pangestu dan Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to evaluate the influence of family and non-family member in the success of family business in trading business in Jabodetabek area. The population of this research is the successor of family business who does business in trading area. The sample of this research is the successor of family business in trading business in Jabodetabek area.  Research methods that are used are questionnaire for 150 respondents. The analytical techniques that are used are classic assumption test, multiple regression analysis, t-test, F test and coefficient determination test using SPSS ver. 20.0. The result of classic assumption stated that this regression model is feasible to be used. The test result shows partially that even together there are still a positive and significance between family member and non-family member involvement for the success of family business. The result of the coefficient determination variable stated that the success of family business can be determined by family and non family member variable percentage that is 67,8% while the rest are determined by other variables.